1997
DOI: 10.2337/diacare.20.8.1329
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Hyperfiltration Is Associated With Blood Pressure Abnormalities in Normotensive Normoalbuminuric IDDM Patients

Abstract: Glomerular hyperfiltration is associated with higher nocturnal diastolic blood pressure and with a blunted nocturnal decrease in diastolic blood pressure levels in normotensive and normoalbuminuric IDDM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 22 publications
7
33
0
1
Order By: Relevance
“…in pharmacological RAAS inhibition (40,41). Importantly, and consistent with previous work in this area, blood pressure was higher in T1D-H (4,42,43). Although this blood pressure elevation within the normal range in T1D-H could be attributed to an elevated systemic sympathetic tone (43), our results suggest that decreased FE Na in euglycemic states may also contribute through increases in total body sodium (44).…”
Section: Discussionsupporting
confidence: 79%
“…in pharmacological RAAS inhibition (40,41). Importantly, and consistent with previous work in this area, blood pressure was higher in T1D-H (4,42,43). Although this blood pressure elevation within the normal range in T1D-H could be attributed to an elevated systemic sympathetic tone (43), our results suggest that decreased FE Na in euglycemic states may also contribute through increases in total body sodium (44).…”
Section: Discussionsupporting
confidence: 79%
“…The association between DN and an increase in absolute BP values in ABPM was demonstrated even during early stages of renal injury 12 . One study carried out by our group in Type 1 DM subjects showed that normoalbuminuric and hyperfiltrating individuals (glomerular filtration >134 ml/ ) presented higher levels of diastolic nocturnal BP when compared to normofiltrating patients 12 .…”
Section: Mean Pressure Values and Diabetes Mellitusmentioning
confidence: 99%
“…SAH is prevalent in patients with Type 2 DM, and is currently present in 30% of cases at the time of DM diagnosis and in up to 73% during the clinical course 1,11 . However, pressure homeostasis modifications can occur in DM patients with no evidence of renal disease 12,13 .…”
Section: Arterial Pressure and Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism(s) responsible for these associations have not been fully elucidated, subjects with uncomplicated type 1 diabetes and high N/D ratio exhibit higher values for GFR in comparison to subjects with a normal N/D ratio (21), and renal hyperfiltration is a risk factor for diabetic nephropathy (22)(23)(24)(25). In one study (26) high N/D ratio was corrected by ACE inhibition, suggesting a role for renin angiotensin system (RAS) activation in this phenomenon.…”
mentioning
confidence: 99%